Clinical electrocardiography - Bayes de Luna, Antoni , 1936- (Wiley-Blackwell, 2012)
"Written by one of the world's most respected cardiologists and designed with the needs of the internist and general clinical cardiologist in mind, this new volume provides clear, accessible guidance on the use of electrocardiography to diagnose and manage cardiovascular disease"--Provided by publisher